Pengaruh Persaingan Bisnis dan Etika Bisnis Islam Terhadap Perilaku Pengusaha Bordir Kawalu Kota Tasikmalaya - Abdillah, Fitriyadi; Nurafipah, Yulia (Jurnal Digital Bisnis, Modal Manusia, Marketing, Entrepreneurship, Finance, & Strategi Bisnis (DImmensi), 2025)
This research aims to analyze the influence of business competition and Islamic business ethics on the behavior of embroidery entrepreneurs in Kawalu, Tasikmalaya City. The research method used a quantitative approach with survey techniques through structured questionnaires. The research sample consisted of 200 embroidery entrepreneurs selected using purposive sampling technique from a total population of 1,056 entrepreneurs. Data were analyzed using multiple linear regression. The results showed that business competition (β=0.465; p<0.05) and Islamic business ethics (β=0.423; p<0.05) had positive and significant effects on the behavior of embroidery entrepreneurs, both partially and simultaneously (F=57.701; p<0.05). These findings imply the importance of developing a healthy business environment and implementing Islamic ethical values in business operations to enhance the competitiveness of the embroidery industry. This research contributes to the development of coaching strategies for embroidery entrepreneurs that emphasize the balance between competition and ethical values in business practices.